A review of integrated photocatalyst adsorbents for wastewater treatment. Issue 6 (December 2018) - Yahya, N.; Aziz, F.; Jamaludin, N.A.; A. Mutalib, M.; Ismail, A.F.; W. Salleh, W.N.; Jaafar, J.; Yusof, N.; A. Ludin, N.
Highlights: Review on the removal of contaminants from wastewaters using photocatalyst, adsorbents and integrated photocatalyst adsorbents. Methods to prepare doping solution of TiO2 and doped-TiO2 properties and performance were extensively discussed. Summarizes major adsorbent which has been integrated with photocatalyst such as carbon, clays, zeolite matrix materials and others. Mechanisms in IPCA were also proposed to clearly understand the possible interactions between organic contaminants and IPCA. Abstract: Photocatalysis has the best potential to replace the conventional wastewater treatment technology due to its utilization of visible light to photo-degrade organic and inorganic contaminants. However, when applied in slurry form, agglomeration of nanoparticle will lead to serious decrease in photocatalytic performance due to hinderance effect. By combining the photocatalyst and adsorbents, which is designated as integrated photocatalyst adsorbent (IPCA), an adsorbent material which also degrades toxic organic compounds in the presence of UV/visible light irradiation could be produced. The compound does not only preserve all the interesting characteristics of both individual components, but also overcomes serious drawbacks, such as low absorptivity, rapid recombination of photogenerated electrons and hinderance effect of photocatalyst when applied in slurry form. There are several criteria that must be obeyed by the absorbent material used such as high absorption capacity to target compound, reasonable transparency to UV–vis light, high surface area, inhibition of photocatalyst leaching and good stability with dispersing solvent. In this review article, the authors presented an overview on the application of photocatalyst, adsorbents and integrated photocatalyst adsorbents for wastewater treatment. Moreover, the discussions were also focused on the major adsorbent which has been integrated with photocatalyst such as carbon, clays, zeolite matrix materials and others. Additionally, the mechanisms of the adsorption of emerging organic contaminants with adsorbents in IPCA were also discussed to clearly understand the possible interactions between organic contaminants and IPCA. Outlook on IPCA study were also discussed to further broaden the prospective of this technology.